FOSTERING LEARNING AUTONOMY THROUGH THE IMPLEMENTATION OF FLIPPED LEARNING IN LANGUAGE TEACHING MEDIA COURSE - Mega Wulandari (Sanata Dharma University Yogyakarta, 2017)
Dealing with millennial generations, it is essential that educators adjust the educational paradigm in order to adapt to the needs of students in the digital age as it is today. This research studied about the implementation of flipped classroom learning model in Language Teaching Media (LTM) to foster fifth semester students’ learning autonomy in English Teacher Education Study Program, Sanata Dharma University. Through the implementation of flipped classroom using Learning Management System (LMS), it is expected to model innovative teaching strategies, such as flipped classrooms, in an effort to prepare preservice teachers for 21st century education. Findings from this research indicated positive perception towards flipped classroom in fostering learning autonomy in terms of planning, classroom engagement and self-evaluation.